Most Recent Data (1996). Statistics Canada. CANSIM: Income, Pensions, Spending and Wealth - Household, Family and Personal Income | Country: Canada | Province: Nunavut | Table: Average personal income (1995 income), population aged 15 and over | Variable: Average personal income (1995 income), population aged 15 and over | Units: $CAD, 1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-119. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Income, Pensions, Spending and Wealth - Household, Family and Personal Income | Country: Canada | Province: Nunavut | Table: Average personal income (1995 income), population aged 15 and over | Variable: Average personal income (1995 income), population aged 15 and over | Units: $CAD, 1996. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-119. Dataset: Presents statistics on components of income (earnings, government transfer payments, pensions, and investments) and income concepts, including market income, total income, income after tax, and the disposable income of individuals, families, and households in Canada. Provided are data on how the incomes of individuals and families change over time, and how family income changes across generations. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Population and Income Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Household Income, Family Income, Earnings, Income